Proceedings of the 1st South Borneo International Conference on Sport Science and Education (SBICSSE 2019) 2020
DOI: 10.2991/assehr.k.200219.059
|View full text |Cite
|
Sign up to set email alerts
|

Agility and Balance on the Speed of Dribbling in Soccer

Abstract: Agility and balance are important in the speed of dribbling in soccer for the student. The main of the research was to identify a level of quantitative changes of the dribbling speed with fifteen years old football players under the influence of the agility and balance. This research method is associative descriptive with regression analysis techniques. The population of this study was all students in the Cigudeg Soccer School amount of 130 people. The sample in this study amounted to 30 people with a purposiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In soccer, weak agility and low balance during dribbling can lead to opponents easily capturing the ball. Therefore, agility significantly influences speed and dribbling skills, and a low agility level makes it challenging to outperform opponent's defense (Abidin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In soccer, weak agility and low balance during dribbling can lead to opponents easily capturing the ball. Therefore, agility significantly influences speed and dribbling skills, and a low agility level makes it challenging to outperform opponent's defense (Abidin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Football is the most popular sport in the world and a high intensity team sport that requires a good amount of physical fitness. Footballers are also required to maintain high levels of aerobic and anaerobic conditioning, strength, Agility, muscle endurance and foot eye coordination [1] . From kinesiological analysis, football is contact sport with high physical demands.…”
Section: Introductionmentioning
confidence: 99%
“…So, to be a successful player in cutting the ball, the inside, outside, and sole of the foot are used. As presented in the previous section, a soccer ball is still the most popular sport in the world [19], [20], and a high-intensity team sport that requires a good amount of physical and physical abilities. Dribbling speed, agility, and strength are among the high levels of aerobic and anaerobic conditioning that soccer players must develop and maintain in the wake of easing in the field performance.…”
Section: Introductionmentioning
confidence: 99%
“…For children, some are well skilled in ball control since the low age whereas others not. Due to this disparity in skills, soccer coaches must work in an integrated manner to ensure a structured and effective program simply known as technical training, and agility in players as the main components of soccer training [20]. Based on the results of observations of the school of a soccer ball at Yogyakarta State University, it has found that there are still many students who have not been able to play football properly, especially in the speed of dribbling [1], [7].…”
Section: Introductionmentioning
confidence: 99%